Analisis Faktor-Faktor yang Mempengaruhi Permintaan Beras di Provinsi Kalimantan Selatan - Dewi, Rosa Chintia; Wardhana, Ali (PPJP ULM, 2022)
This study was to determine the effect of rice prices, corn prices, rice production, and population simultaneously and partially on demand for rice in South Kalimantan Province in 2010-2019.This research was conducted in South Kalimantan using secondary data and then tested using a multiple linear regression analysis model by looking at the test results consisting of a partial test (t test) and simultaneous test (F test).The results of this study indicate that simultaneously the price of rice, corn price, rice production, and population have a significant effect on demand for rice in South Kalimantan Province. The partial test results show that the price of rice and total population have a significant effect, while the price of corn and rice production do not have a significant effect on demand for rice in South Kalimantan Province.